Exploring the factors affecting career progression in informal faculty mentoring sessions within mentor and mentee relationships: a qualitative study - Manahil Niazi; Usman Mahboob; Neelofar Shaheen; Shazia Gul; Muhammad Humza Bin Saeed; Amber Kiyani (BMC Medical Education)
Abstract Background Mentoring plays a pivotal role in mentees’ professional advancement. However, the factors that affect career progression in informal mentoring relationships, especially with respect to faculty members, have not been extensively explored. This study aimed to explore the factors that affect career progression in informal faculty mentorings within mentor and mentee relationships. Methodology A Qualitative Exploratory Study was designed and conducted from May to October 2023. Faculty members with informal mentoring relationships were recruited through purposive sampling. Seven faculty mentors and eight faculty mentees from various institutions participated in the study. Semi-structured interviews were used to collect data, which were audio-recorded and verbatim transcribed. The transcripts were then analysed using NVivo Software and coded. Braun and Clark’s framework was used for the thematic analysis. The study adhered to the COREQ (Consolidated Criteria for Reporting Qualitative Research) checklist to ensure comprehensive and transparent reporting of the qualitative research process. Results A total of 76 codes emerged which were classified into six themes: (1) an ideal mentee, (2) an ideal mentor, (3) factors promoting the relationship, (4) the role of gender, (5) factors deteriorating the relationship, (6) overcoming barriers / trust-building strategies. Within each theme, mentor–mentee needs and behaviours were identified, which could lead to positive or deteriorating outcomes. Conclusion Factors affecting career progression in informal faculty mentoring sessions include mentees' positive mindset, internal motivation and clarity of vision, mentors' skills, reputation, and role modelling. Effective communication, trust, respect, and clear goals are also essential. Challenges, such as busy schedules, cross-gender mentoring, and societal biases, affect these relationships. Overcoming these barriers involves sharing experiences, psychosocial support, empathy, active listening, and feedback.